Frontiers in water-energy-nexus -- nature-based solutions, advanced technologies and best practices for environmental sustainability : proceedings of the 2nd WaterEnergyNexus Conference, November 2018, Salerno, Italy /: proceedings of the 2nd WaterEnergyNexus Conference, November 2018, Salerno, Italy. (2020) - Unknown
No abstract available